Paclitaxel alleviated sepsis-induced acute lung injury by activating MUC1 and suppressing TLR-4/NF-κB pathway - Wang YM; Ji R; Chen WW; Huang SW; Zheng YJ; Yang ZT; Qu HP; Chen H; Mao EQ; Chen Y; Chen EZ (Dove Medical Press, 2019)
Yu-Ming Wang,1,* Ran Ji,1,* Wei-Wei Chen,1 Shun-Wei Huang,1 Yan-Jun Zheng,1 Zhi-Tao Yang,1 Hong-Ping Qu,2 Hao Chen,3 En-Qiang Mao,1 Ying Chen,1 Er-Zhen Chen1 1Department of Emergency, Ruijin Hospital Affiliated to Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 2Department of Critical Care Medicine, Ruijin Hospital Affiliated to Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 3Department of General Surgery, Ruijin Hospital Affiliated to Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ying Chen; Er-Zhen ChenDepartment of Emergency, Ruijin Hospital Affiliated to Shanghai Jiao Tong University School of Medicine, No. 197 Ruijin 2nd Road, Shanghai 200025, ChinaTel +86 216 437 0045Fax +86 216 433 3548Email bichatlion@163.com; chenerzhen@hotmail.comPurpose: It has been reported that approximately 40% of ALI (acute lung injury) incidence resulted from sepsis. Paclitaxel, as a classic anti-cancer drug, plays an important role in the regulation of inflammation. However, we do not know whether it has a protective effect against CLP (cecal ligation and puncture)-induced septic ALI. Our study aims to illuminate the mitigative effects of paclitaxel on sepsis-induced ALI and its relevant mechanisms.Materials and methods: The survival rates and organ injuries were used to evaluate the effects of paclitaxel on CLP mice. The levels of inflammatory cytokines were tested by ELISA. MUC1 siRNA pre-treatment was used to knockdown MUC1 expression in vitro. GO203 was used to inhibit the homodimerization of MUC1-C in vivo. The expression levels of MUC1, TLR 4 and p-NF-κB/p65 were detected by Western blot.Results: Our results showed that paclitaxel improved the survival rates and ameliorated organ injuries especially lung injury in CLP-induced septic mice. These were accompanied by reduced inflammatory cytokines in sera and BALF (bronchoalveolar lavage fluid). We also found paclitaxel could attenuate TLR 4-NF-κB/p65 activation both in lung tissues of septic mice and LPS-stimulated lung type II epithelial cell line A549. At the upstream level, paclitaxel-upregulated expression levels of MUC1 in both in vivo and in vitro experiments. The inhibitory effects of paclitaxel on TLR 4-NF-κB/p65 activation were reversed in lung tissues of septic mice pre-treated with MUC1 inhibitor and in MUC1-knockdown A549 cells. Protection of paclitaxel on sepsis-induced ALI and decrease of inflammatory cytokines were also abolished by inhibition of MUC1.Conclusion: Collectively, these results indicated paclitaxel could significantly alleviate acute lung injury in CLP-induced septic mice and LPS-stimulated lung type II epithelial cell line A549 by activating MUC1 and suppressing TLR-4/NF-κB pathway.Keywords: sepsis, acute lung injury, MUC1, TLR 4, NF-κB